Improving The Quality of Qur’an Recitations at Majelis Ta’lim Al-Hasanah, Gebang Raya Village - Abdul Wapa; Mohamad Asrori Mulky (International Research and Development for Human Beings (IRDH), 2025)
This article aims to improve the ability to read the Qur'an with Fashohah and Tajweed. Reading the Qur'an can pronounce what is written in the holy book of the Qur'an well and correctly according to the makhraj and the rules of tajweed science, so that we know that reading the Qur'an must be good and correct and know the makhorijul letters and when to stop (waqaf) and continue (washol), so that the pronunciation of the Qur'an is perfect. Al-Hasanah Ta'lim Assembly is a place of education for the Qur'an and Religious Sciences that teaches children according to their age, so this study discusses the improvement of reading the Qur'an at the Al-Hasanah Ta'lim Assembly so that this study uses a qualitative method using a field study approach. According to Dedy Mulyana, field research is a type of research that studies phenomena in its natural environment. Al-Hasanah Ta'lim Assembly teaches the reading of the Qur'an every night precisely after Maghrib which has 25 students.